Clinical outcome of shoulder muscle transfer for shoulder deformities in obstetric brachial plexus palsy: A study of 150 cases - Mukund R Thatte; Mandar V Agashe; Aamod Rao; Chasanal M Rathod; Rujuta Mehta (Indian Journal of Plastic Surgery)
Background: Residual muscle weakness, cross-innervation (caused by misdirected regenerating axons), and muscular imbalance are the main causes of internal rotation contractures leading to limitation of shoulder joint movement, glenoid dysplasia, and deformity in obstetric brachial plexus palsy. Muscle transfers and release of antagonistic muscles improve range of motion as well as halt or reverse the deterioration in the bony architecture of the shoulder joint. The aim of our study was to evaluate the clinical outcome of shoulder muscle transfer for shoulder abnormalities in obstetric brachial plexus palsy. Materials and Methods: One hundred and fifty patients of obstetric brachial plexus palsy with shoulder deformity underwent shoulder muscle transfer along with anterior shoulder release at our institutions from 1999 to 2007. Shoulder function was assessed both preoperatively and postoperatively using aggregate modified Mallet score and active and passive range of motion. The mean duration of follow-up was 4 years (2.5-8 years). Results: The mean preoperative abduction was 45° ± 7.12, mean passive external rotation was 10° ± 6.79, the mean active external rotation was 0°, and the mean aggregate modified Mallet score was 11.2 ± 1.41. At a mean follow-up of 4 years (2.5-8 years), the mean active abduction was 120° ± 18.01, the mean passive external rotation was 80° ± 10.26, while the mean active external rotation was 45° ± 3.84. The mean aggregate modified Mallet score was 19.2 ± 1.66. Conclusions: This procedure can thus be seen as a very effective tool to treat internal rotation and adduction contractures, achieve functional active abduction and external rotation, as well as possibly prevent glenohumeral dysplasia, though the long-term effects of this procedure may still have to be studied in detail clinico-radiologically to confirm this hypothesis. Level of evidence: Therapeutic level IV